2008
DOI: 10.1557/jmr.2008.0062
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of oxidation-resistance of NiCrAlY coatings by application of CrN or CrON interlayer

Abstract: NiCrAlY coatings with and without CrN or CrON interlayer as diffusion barrier were deposited on superalloy DSM11 by arc ion plating (AIP). The oxidation performance of the coating systems was evaluated by isothermal oxidation tests at 1100°C for 100 h. The element interdiffusion and oxidation behavior of the coating systems were described. It was found that the NiCrAlY coatings provided protective effect for the DSM11 substrate. However, serious interdiffusion between the coatings and substrate resulted in rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Different TM nitride coatings have been synthesised and investigated due to their high hardness, good oxidation resistance, and low wear rate in dry atmosphere, as well as their phase stability in corrosive environments [10,15,[33][34][35][36][37]. Oxynitride coatings have also been studied due to their plasmonic properties, relatively low electrical resistivity, good biocompatibility, and high oxidation resistance [25,[38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Different TM nitride coatings have been synthesised and investigated due to their high hardness, good oxidation resistance, and low wear rate in dry atmosphere, as well as their phase stability in corrosive environments [10,15,[33][34][35][36][37]. Oxynitride coatings have also been studied due to their plasmonic properties, relatively low electrical resistivity, good biocompatibility, and high oxidation resistance [25,[38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a dense, continuous and closed-packed structure Al 2 O 3 exhibits outstanding diffusion barrier ability [4]. The presence of defects, such as grain boundaries, cracks and pores in the diffusion barrier will definitely decrease its competence due to the increase of short-circuit diffusion paths [14].…”
Section: Oxidation Resistance and Diffusion Barrier Mechanismmentioning
confidence: 99%
“…In previous studies [4][5][6][7][8] it was found that the coating system of MCrAlY overlayer with a CrN diffusion barrier had a strong interfacial strength, but the oxidation resistance of the duplex coatings was limited. On the other hand, the introduction of a pure Cr 2 O 3 diffusion barrier can suppress the interdiffusion with high efficiency due to the formation of a dense Al 2 O 3 interlayer during thermal treatment, although the interfacial strength is impaired by the presence of residual stresses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations